STATUS KERENTANAN NYAMUK ANOPHELES SPP TERHADAP LAMBDACYHALOTHRIN 0.05% DI KECAMATAN PITURUH KABUPATEN PURWOREJO - Angelia Galuh Ningtyas; M. Arie Wuryanto; Lintang Dian Saraswati; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Anopheles spp is a malaria mosquito vector in Purworejo Regency. The monitoring of the susceptibility status of Anopheles spp to insecticides not implemented. The purpose of this study was to determine the susceptibility status of Anopheles spp mosquitoes in Pituruh Subdistrict. The design of this study used quasi-experiment with samples of Anopheles spp mosquitoes as a result of F1 colonization The mosquitoes used for testing are female Anopheles spp mosquitoes. The total number of mosquitoes tested was 120 mosquitoes. Repetition was carried out 6 times with the details of 4 tubes as a treatment and 2 tubes as controls for each tube containing 20 mosquitoes. The results showed that the average knock down of Anopheles spp mosquitoes during the 60-minute exposure was 19 per repetition (92.5%). After a 24-hour holding, the average mortality of Anopheles spp mosquitoes was 20 per repetition (100%). Mosquito deaths reached 80 mosquitoes (100%) at 12 hours. In the control group, the number of mosquito deaths after 24 hours holding was 2 tails (0.5%), so there was no need to make corrections using the Abbots formula. Anopheles spp mosquitoes are said to be susceptible to lambdacyhalothrin so lambdacyhalothrin can still be used as vector control in Purworejo Regency.